Anemia has an impact on prognosis in heart failure with preserved ejection fraction with mild chronic kidney disease. (June 2021) - Okuno, Keisuke; Naito, Yoshiro; Asakura, Masanori; Sugahara, Masataka; Horimatsu, Tetsuo; Yasumura, Seiki; Tahara, Saki; Nagai, Toshiyuki; Saito, Yoshihiko; Yoshikawa, Tsutomu; Masuyama, Tohru; Ishihara, Masaharu; et al.
Abstract: Background: Anemia and chronic kidney disease (CKD) are common in patients with heart failure with preserved left ventricular fraction (HFpEF). However, it is entirely unknown about the impact of anemia on prognosis in HFpEF patients with CKD. In this study, we investigated the impact of anemia on prognosis and the optimal hemoglobin (Hb) levels to predict prognosis in HFpEF patients with CKD. Methods and Results: We prospectively examined 523 consecutive HFpEF patients enrolled in Japanese heart failure syndrome with preserved ejection fraction registry. CKD was defined as an estimated glomerular filtration rate (eGFR) of <60 mL /min/1.73 m 2 . The prevalence rate of anemia was 78% in HFpEF patients with CKD by using the World Health Organization criteria. Kaplan-Meier analysis for all-cause mortality and heart failure rehospitalization demonstrated that anemic patients had poor prognosis compared with non-anemic patients in HFpEF patients with CKD, but not those without CKD. According to the degree of CKD, anemia affected prognosis in HFpEF patients with mild CKD (45 ≤ eGFR < 60), but not those with moderate to severe CKD (15 ≤ eGFR < 45). Additionally, multivariate analysis revealed that anemia and Hb levels were independent predictors of composite outcomes in HFpEF patients with mild CKD, but not those with moderate to severe CKD. Finally, survival classification and regression tree analysis showed that the optimal Hb levels to predict composite outcomes were 10.7 g/dL in those with mild CKD. Conclusions: Anemia has an impact on prognosis in HFpEF patients, especially among those with mild CKD.